SPE Asia Pacific Oil &Amp; Gas Conference and Exhibition 2014
DOI: 10.2118/171454-ms
|View full text |Cite
|
Sign up to set email alerts
|

Wellbore Stability Modelling for Horizontal and Multibranch Lateral Wells in CBM: Practical Solution to Better Understand the Uncertainty in Rock Strength and Coal Heterogeneity

Abstract: Arrow Energy has engaged in drilling production Coal Bed Methane (CBM) wells in the Bowen Basin. As part of its field development strategy, varied styles of horizontal wells have been planned and executed along the coal targets of Moranbah Coal Measures (MCM). Some of the recently drilled multi-branch lateral and horizontal wells experienced different drilling challenges and production performance. Potential geomechanical issues such as borehole conditions and fines/solid production are directly related to wel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…Since the engineering factors have significant impacts on the gas production, , the production behavior of each well should be analyzed before conducting the history matching for the individual wells. It was found that most low producers used open annulus and gravel-packed completion types, and the abnormal low production at a particular period was usually affected by the unreasonable drainage working systems, such as a sudden decrease in BHFP and noncontinuous dewatering.…”
Section: History Matching Processmentioning
confidence: 99%
“…Since the engineering factors have significant impacts on the gas production, , the production behavior of each well should be analyzed before conducting the history matching for the individual wells. It was found that most low producers used open annulus and gravel-packed completion types, and the abnormal low production at a particular period was usually affected by the unreasonable drainage working systems, such as a sudden decrease in BHFP and noncontinuous dewatering.…”
Section: History Matching Processmentioning
confidence: 99%
“…Coal fines are a common issue in almost all major CSG fields globally, such as in Bowen Basin (Australia), San Juan Basin (USA), Qinshui Basin (China), and Junggar Basin (China) . Coal fines are small particles released from the coal and mainly consist of nonorganic minerals like clay, kaolinite, quartz, and others. ,, They can be divided into two types: (i) primary coal fines, which refer to the coal fines that already exist before the production, and (ii) secondary coal fines, which are production induced. , More coal fines are observed during the dewatering and two-phase flow stages than in other stages, , as illustrated in Figure .…”
Section: Coal Fines/solids Generationmentioning
confidence: 99%
“…Coal fines are a common issue in almost all major CSG fields globally, such as in Bowen Basin (Australia), 201 San Juan Basin (USA), 202 Qinshui Basin (China), 203 and Junggar Basin (China). 204 Coal fines are small particles released from the coal and mainly consist of nonorganic minerals like clay, kaolinite, quartz, and others.…”
Section: Coal Fines/solids Generationmentioning
confidence: 99%